2015
DOI: 10.1177/2325967115s00119
|View full text |Cite
|
Sign up to set email alerts
|

The Costs Associated With The Perioperative Management Of Articular Cartilage Lesions In The United States

Abstract: Objectives:There is a large and increasing U.S. population with symptomatic focal chondral/osteochondral lesions of the knee. The use of cartilage repair and restoration procedures has increased over the past decade due to significant improvements in diagnosis, surgical indications/technique, and graft resources. While clinical evidence supports utilization of these procedures, the costs associated with the perioperative management of these patients and the specific procedures are unknown. Given current challe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 0 publications
0
12
0
Order By: Relevance
“… a Continuous data are given as a mean ± SD. No cost is listed for next-generation ACI because it was not included in the Zhang et al 32 publication and there were not enough data on the pre- and postoperative costs associated with this procedure to accurately estimate these costs ourselves. ACI-1, first-generation autologous chondrocyte implantation; ACI-2, next-generation autologous chondrocyte implantation; MFx, microfracture; OAT, osteochondral autograft transplantation.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“… a Continuous data are given as a mean ± SD. No cost is listed for next-generation ACI because it was not included in the Zhang et al 32 publication and there were not enough data on the pre- and postoperative costs associated with this procedure to accurately estimate these costs ourselves. ACI-1, first-generation autologous chondrocyte implantation; ACI-2, next-generation autologous chondrocyte implantation; MFx, microfracture; OAT, osteochondral autograft transplantation.…”
Section: Resultsmentioning
confidence: 99%
“…The total costs associated with MFx, OAT, and ACI-1 were determined from a recent publication based on review of a national private insurance database. 32 The charges for each procedure, including for the 1-year preoperative and 1-year postoperative periods, were calculated for each patient. Charges included in this analysis were imaging, outpatient visits, rehabilitation, joint injections, and repeat procedures for postoperative complications.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A US retrospective review from 2015 based on PearlDiver, a national private insurance database, examined the preoperative and postoperative costs for the evaluation as well as surgical treatment of symptomatic focal cartilage defects in the knee. 32 Costs included outpatient visits, imaging, rehabilitation, joint injections, and repeat procedures in case of postoperative complications. Among others, ACI (546 patients) and MFX treatments (38,444 patients) were analyzed, with costs amounting to $16,016.70 (∼€14,205) in MACI-treated patients and $7258.51 (∼€6402) in MFX-treated patients in a time horizon from 1 year preoperatively to 1-year postoperative follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding costs associated with secondary procedures, the present study found in contrast that MACI was associated with lower costs than MFX treatment. The deviation in the latter aspect might be caused by the comparison with first-generation ACI, the shorter observational period of 2 years (1 preoperative year as well as 1 postoperative year), and the sparse information regarding the definition of secondary procedures in the Zhang et al 32 study.…”
Section: Discussionmentioning
confidence: 99%